Introduction to transport policy a public policy view - Stopher, Peter R. (Cheltenham, Edward Elgar, 2014)
This comprehensive and accessible textbook introduces the basic concepts of transport policy and decision-making to students of transport policy, transport planning, urban transport, transport evaluation and public policy.
Includes bibliographical references and index.
Keywords: Transportation and state